AB0095 IL-21R signature in synovial tissue and blood of patients with rheumatoid arthritis. (23rd January 2014) - Frleta, M.; King, V.; Reilly, J.H.; Kerr, S.; Gilchrist, D.S.; Tornehave, D.; Neisig, A.; Lundsgaard, D.; Miller, A.M.; McInnes, I.B.
Abstract : Background: Cytokines regulate a broad range of inflammatory pathways in the pathogenesis of Rheumatoid Arthritis (RA), and cytokine blockade against TNF-a and IL-6 has offered substantial advances in the treatment of articular inflammation. However, a large proportion of patients become unresponsive or exhibit only a partial response to treatment and new therapies are thus required. IL-21 is a member of the four-a-helix bundle family of cytokines that mediates pleiotropic effects through the IL-21 receptor (IL-21R)[1]. Since potency of IL-21 is mainly dependent on presence and abundance of its receptor on different cell types, the objective of this study was to characterize expression of IL-21R in the synovium and blood of patients with RA. Methods: Immunohistochemistry for IL-21R was carried out on synovial tissue samples derived by arthroplasty from patients with RA (n=5) obtained from our synovial tissue bank. Peripheral blood mononuclear cells (PBMC) from 10 RA patients and 6 healthy subjects were isolated using Histopaque (Sigma). Cells were analyzed by flow cytometry for IL-21R expression on T cells (CD3/CD4/CD8), B cells (CD19/CD27) and NK cells (CD16/CD56). In parallel, RNA was purified from total PBMC using Qiagen RNeasy kit, converted into cDNA using Quantitect reverse transcription kit (Qiagen) and the absolute levels of IL-21R transcripts measured by quantitative Real-Time PCR. Samples were normalized against endogenous GAPDH control. Results: Expression of IL-21R was detected in all synovial RA tissues tested. The IL-21R + cells were located in the synovial intimal and sub-lining layers and in lymphoid aggregates. Flow cytometric analysis of PBMC revealed IL-21R highly expressed on both CD4 + (12.58 mean fluorescent intensity (MFI)) and CD8 + (13.69 MFI) T cells, as well as on a subset of NK cells (19.15 MFI) in RA patients. Interestingly, the amount of IL-21R per CD8 + T cell is higher in patients with RA than in healthy subjects (13.69 MFI vs. 5.06 MFI, p=0.007, respectively). On B cells, IL-21R expression was higher on the CD27 - fraction of naïve B cells (37.02 MFI), with lower expression on the CD27 + memory B cells (32.22 MFI). In this study cohort, Real-Time PCR revealed IL-21R to be at significantly higher transcript levels in total PBMC of healthy subjects compared to RA patients (2239 vs. 827.3 mean gene copy numbers, normalized to 10 4 copy numbers of GAPDH, p=0.001, respectively), suggesting discordant mRNA and protein expression indicating complex regulation of IL-21R biology. Conclusions: Our results show abundant expression of IL-21R in synovial tissue as well as peripheral blood of RA patients. Diversity in the signature between RA patients and healthy volunteers requires further phenotyping at the protein as well as transcriptional level. Such data will be essential in translating to proof of concept clinical trials. References: Habib T. et al., J Allergy Clin Immunol. 2003 Dec;112(6):1033-45. Disclosure of Interest: M. Frleta: None Declared, V. King: None Declared, J. Reilly: None Declared, S. Kerr: None Declared, D. Gilchrist: None Declared, D. Tornehave Shareholder of: Minor stock holder at Novo Nordisk A/S, Employee of: Novo Nordisk A/S, A. Neisig Employee of: Novo Nordisk A/S, D. Lundsgaard Shareholder of: Minor stock holder at Novo Nordisk A/S, Employee of: Novo Nordisk A/S, A. Miller: None Declared, I. McInnes: None Declared